Glycerol concentration sensor based on the MIM waveguide structure - Xu, Qining; Zhu, Jun (Frontiers in Physics, 2022)
Glycerol is widely used in medicine, industry and skin care products. This study investigated a high-sensitivity glycerol concentration sensor based on double Fano resonances in a metal-insulator-metal (MIM) waveguide structure, established a coupling model of a baffle waveguide (BW) and a circular split ring resonator (CSRR), and generated asymmetric double Fano resonances in the waveguide structure. The Fano resonance transmittance reached 0.82, and the linear relationship between the refractive index (RI) and the glycerol concentration was obtained using the sensitivity of the Fano resonance spectrum. The application of the proposed sensor for glycerol concentration detection revealed that the Fano resonance wavelength was redshifted with the RI and that the sensing sensitivity reached 1153.85 nm/refractive index unit (RIU); therefore, the quick detection of the corresponding glycerol concentration can be realized. This proposed structure has significance in the research of optical sensors and optical switches.